THE INNOVATIVE APPROACHES TO THE PROBLEM OF RESOURCE SAVING FOR DAIRY INDUSTRY ENTERPRISES - Anatoly Viktorovich Permyakov; Natalia Viktorovna Balandina; Maria Ivanovna Shramko; Oksana Nikolaevna Kolomyts (Современная наука и инновации, 2022)
The article deals with the problem of resource saving on dairy industry enterprises in Russia. Based on the analysis of the current state of the industry some recommendations to address this problem have been offered, the basic activity directions of resource saving of enterprises have been determined. A special attention is paid to secondary raw materials, such as whey, and lactose reception.